PERCEPTIONS OF ATTITUDES, VALUES AND BELIEFS OF HEALTH SCIENCE STUDENTS AND STAFF ON TEAM-BASED CARE. (11th November 2018) - Bakerjian, D; Marin-Cachu, A; Edwards, J; Rodgers, J; Johnson, M
Abstract: The goal of SPLICE is to develop, test and disseminate a primary care (PC) educational and training model to improve team-based care. The initiative includes a collaborative practice, educational curriculum for FNP, PA, RN and medical students and PC medical and pharmacy residents implemented in a community FQHC. The capacity of the PC workforce continues to be insufficient to meet the needs of a growing aging population. Experts advocate building geriatric capacity by utilizing a team approach; however, studies have shown that few professional programs include education on team science or team care. Validated tools were used to create a web-based survey to obtain baseline and post-training data about perceptions and attitudes related to interprofessional teams, values and beliefs, roles and responsibilities, and patient-centered care. Response fields included both free text and Likert scale (range 1=strongly disagree to 5=strongly agree). The baseline survey was administered to all learners (n=84) including licensed (MD, PA, FNP, RN) and unlicensed staff (MA, office assistants, etc.). Key findings highlighted that interprofessional biases exists for some learner groups (mean=3.54, p=0.009). Most members agreed that respect, trust, and ethical conduct are important to IP teamwork (mean=4.63/5). There were differences of perception of mutual support between types of team members (mean 4.56, p=0.031). Communication was identified as a key area for improvement. The survey provided an excellent basis for the development of the team-based education program. Interprofessional bias, communication and mutual support, and trust are areas for improvement and focused training opportunities.